Pengaruh Literasi Keuangan, Sikap Keuangan, dan Pendidikan Keuangan Keluarga Terhadap Manajemen Keuangan Pribadi dengan Locus Of Control Sebagai Variabel Intervening - Ihda Rohmatin Khoirunnisa; Rochmawati Rochmawati (Jurnal Pendidikan Akuntansi (JPAK), 2021)
Personal financial management needs to be done by every individual including students. However, not all individuals are accustomed to doing personal financial management. Personal financial management in students is thought to be influenced by financial literacy, financial attitudes, and family financial education through locus of control as an intervening variable. The purpose of this study was to analyze the direct and indirect effects of financial literacy, financial attitudes, and family financial education on personal financial management with locus of control as an intervening. Quantitative research is the type of research used. Questionnaires are used as data collection. The total population of the study was 158 students of Accounting Education, State University of Surabaya, class of 2017 and 2018. Purposive sampling was used for sampling. Classical assumption test, regression analysis, path analysis and Sobel test were used as data analysis techniques and used SPSS 16.0 software. This study resulted in 1) the direct influence of financial literacy, financial attitudes, and family financial education on personal financial management. 2) There is an indirect effect of locus of control on personal financial management. 3) There is an indirect influence of financial literacy, financial attitudes, and family financial education on locus of control 4) Locus of control is not an intervening variable of financial literacy on personal financial management . 5) locus of control is an intervening variable of financial attitudes and family financial education on personal financial management.